PENGARUH KEHARMONISAN KELUARGA TERHADAP PERILKU MENYIMPANG PADA SISWA SMA NEGERI 2 POLEWALI MANDAR KELAS X PEMINATAN ILMU-ILMU SOSIAL - Andi Algazali; Mansyur Radjab; Dwia Aries Tina (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
This study aims to describe and analyze the effect of family harmony on deviant behavior in Polewali 2 high school students in class X specialization in social sciences. This research uses quantitative methods to 36 respondents of Polewali Class X SMA 2 students who are interested in social sciences selected proportionally random sampling. The data analysis technique uses simple regression test statistics with the help of the statististical program for social science (SPSS) program. The results of the study showed that there was an effect of family harmony on the occurrence of deviant behavior in students of Polewali State High School 2 class X specialization in the social sciences with the influence of family harmony towards deviant behavior. Thus family harmony has a positive effect on deviant behavior. This positive effect means that the increasing harmony of family students will influence the decline of deviant behavior in public high school students 2 Polewali Specialization in Social Sciences.